Effect of heat treatment on the damage ratio of corroded ST 60 MN steel (2001)
In this work, the effect of various heat treatments on ST 60Mn steel on its fatigue strength prior to use and after use studied. It was observed that by nomalising for service conditions not exceeding 106 stress cycles, the fatigue stregnth was raised by a factor of 1.2